Social Interaction In Culinary Business: A Case Study Of Food Vendors On Hercules Road, Ulin Cornerstone - Maimunah, Siti; Rahmawati, Linda Puteri; ridhaa, Ridha Safitri (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
The social interaction in the food industry is the focus of this research, particularly at the food vendors on Hercules road in Ulin cornerstone. Observation is the study method employed, and a checklist is utilized to collect data. It is evident from observations that traders make eye contact, approach, smile, nod, and shake their heads, among other social interactions. In the culinary industry, ties between customers and suppliers are forged through social interaction. The observations reveal that trader 1, trader 2, and trader 3 have different social interaction tendencies. Traders 2 and 3 exhibit a wider variety of social interaction patterns compared to trader 1, who tends to be more optimistic and avoid confrontation. Additionally, there are distinctions between them in how they greet, enquire, converse, laugh, and negotiating with buyers.